2016
DOI: 10.1007/s10064-015-0841-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of compression in well-graded saprolitic soils

Abstract: Soils originating from weathering processes present considerable heterogeneity in their composition, which can make it difficult to analyse their behaviour in a systematic way. For the granitic saprolites discussed in this paper, based on a trend between soil density and weathering degree, there appears to be two different domains of behaviour, a granular domain and a clay matrix one, according to the degree of weathering reached. Recognition of these domains can reduce the apparent scatter of data for the eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…[5]). Rocchi and Coop [21] found the same trend for the tests at the same maximum stress for their study on well graded saprolitic soils. Also, they stated that the particles in a loose state will have lesser contact points between each other and therefore experience larger stresses.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…[5]). Rocchi and Coop [21] found the same trend for the tests at the same maximum stress for their study on well graded saprolitic soils. Also, they stated that the particles in a loose state will have lesser contact points between each other and therefore experience larger stresses.…”
Section: Resultssupporting
confidence: 67%
“…It has been observed that maximum grain size seems to dominate breakage rather than the amount of fines in a mixture [27]. For the granitic saprolites, the particle breakage has been linked to the quantity of large particles and their characteristics [21]. For the samples presented in this paper, the maximum grain size is the same (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Residual soils such as granitic saprolite soils originated from the chemical and physical weathering processes of granite rock, thus the mineralogy and micro-fabric of the parent rock are considered substantial factors governing the resulted soils behavior [1]. Residual soils are generally well-graded and include a broad domain of grain size distributions [2]. Many studies have shown that the grading of granitic saprolite soil depends on the environmental circumstances of the weathering process, mineralogy and micro-fabric of the parent rock; in which the soil grading curve shifts towards the fine domain as the weathering grade increases [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…On account of shortage and insufficient data available about mineral composition of soils in addition to grains morphology, researchers have concluded that grading is considered the dominant factor in the compressive behavior of saprolitic soils [2,7]. Ham, Nakata [8] found that content of gravel had a significant impact on the compression characteristics of CDG soils.…”
Section: Introductionmentioning
confidence: 99%